The Role of Spirituality in Management Education - Keefner, Jenna (2025)
Spirituality, distinct from religion, is framed in the scope of this paper as a search for meaning, connection, and ethical grounding in the context of educational leadership and management. By synthesizing insights from anthropology, psychology, and management theory, the study investigates the potential of spiritual principles intersecting with leadership practices, emotional intelligence, and organizational ethics.